Fully epitaxial giant magnetoresistive devices with half-metallic Heusler alloy fabricated on poly-crystalline electrode using three-dimensional integration technology. (November 2020) - Chen, Jiamin; Sakuraba, Yuya; Yakushiji, Kay; Kurashima, Yuichi; Watanabe, Naoya; Liu, Jun; Li, Songtian; Fukushima, Akio; Takagi, Hideki; Kikuchi, Katsuya; Yuasa, Shinji; Hono, Kazuhiro
Abstract: Fully-epitaxial magnetoresistance (MR) devices with half-metallic Heusler alloys has attracted considerable attention for years due to their excellent spin-dependent transport properties such as high MR ratio and ultra-low resistance-area product. However, their poor manufacturability due to the necessity of epitaxial growth on a special single crystalline substrate such as MgO(001) hinders their practical applications. To overcome this issue, in this study, we fabricated Heusler-based epitaxial current-perpendicular-to-plane giant magnetoresistance (CPP-GMR) film grown on Si substrate and directly bonded it to poly-crystalline electrode wafer by using three-dimensional (3D) integration processes such as direct wafer bonding and removal of backside Si substrate. First we explored suitable seed/buffer layers for the (001)-oriented epitaxial growth of Heusler CPP-GMR on Si(001) substrate. Si-subs/NiAl/CoFe seed/buffer structure was found to induce (001)-oriented epitaxial growth and to suppress an Al diffusion from NiAl to the Heusler electrode even after annealing at 500 °C, resulting in large MR ratio comparable to that with MgO substrate. After direct wafer bonding process, the microstructure analysis revealed clean damage-free bonded interface between the epitaxial Heusler GMR and poly-crystalline electrode films with Au capping layers. After the 3D integration processes, high MR performance has been successfully reproduced. This unique processing method enables the integration of high performance Heusler-based epitaxial spintronic devices for various practical applications. Graphical abstract: Image, graphical abstract